Investigation of some of the factors influencing fingermark detection. (August 2018) - Chadwick, Scott; Moret, Sebastien; Jayashanka, Nilesh; Lennard, Chris; Spindler, Xanthe; Roux, Claude
Highlights: Over 14, 000 fingermarks were developed and evaluated to investigate some of the factors that influence fingermark detection. Fingermarks deposited on porous surfaces were more likely to be developed than fingermarks on non-porous surfaces. Significant variability was observed between donors and within repeat depositions of the same donors fingermarks. Reinforces the need for further research into the fundamentals of fingermark detection. Abstract: The primary aims of fingermark detection research are to improve the quality and increase the rate of detection of identifiable impressions. This is usually performed through the development of new methods and technologies to provide alternatives to or improve current procedures. While research of this nature is important to pursue, it fails to address the underlying question related to the factors that affect the detection of a latent fingermark. There has been significant research that has examined the differences between techniques, donors and fingermark age, as well as the composition of latent fingermarks. However, they tend not to focus on determining how these factors influence the quality of the developed mark. This study involved the development and evaluation of over 14, 000 natural fingermarks deposited on a variety of surfaces to examine the effect of substrate, age, donor variability (both inter- and intra-), depletions and type of finger on fingermark development. Fingermarks were deposited on four substrates (two non-porous and two porous) and developed with either indanedione-zinc (IND-Zn) or cyanoacrylate followed by rhodamine 6G staining (CA + R6G). Three independent assessors graded each mark on the quality of development using an absolute scale proposed by the UK Centre for Applied Science and Technology (CAST). The data generated from these assessments were then analysed for trends or other useful insights. The results from this work reaffirm that individual substrate characteristics (and the choice of development technique) play a significant role in determining the number and quality of marks developed. It was found that fingermarks were more likely to be detected on porous substrates and to also be of a higher quality than on non-porous. The effect of fingermark donor variability was also explored, with significant differences observed between donors and within donors. This research shows that current detection techniques do not detect all available fingermarks, reinforcing the need for further research into the fundamentals of fingermark detection in order to gain a better understanding of the techniques currently used. The study has identified considerations for the development of novel techniques and how we need to account for variability when designing fingermark research experiments.